2018
DOI: 10.13057/biodiv/d200115
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative morphological diversity of female Pelung Chickens in West Java, Indonesia

Abstract: Asmara IY, Garnida D, Tanwiriah W, Partasasmita R. 2019. Qualitative morphological diversity of female Pelung Chickens in West Java, Indonesia. Biodiversitas 20: 126-133. Pelung chickens are indigenous chickens in Indonesia derived from Cianjur District, West Java Province. The chickens which are raised as singing chickens have a distinctive body shape compared to other local chickens. Regular contests are conducted as a media to show singing ability and performance including morphological characteristics of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
2
11
4
2
Order By: Relevance
“…Our results are in agreement with a previous finding by Syakir [17], who observed wild as the most frequent plumage pattern in Gaga chickens. A study by Asmara et al [7] found that black was the most predominant plumage pattern in female Pelung chickens, but in our study, black ranked third.…”
Section: Plumage Patterncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our results are in agreement with a previous finding by Syakir [17], who observed wild as the most frequent plumage pattern in Gaga chickens. A study by Asmara et al [7] found that black was the most predominant plumage pattern in female Pelung chickens, but in our study, black ranked third.…”
Section: Plumage Patterncontrasting
confidence: 84%
“…There was no variation in plumage color observed in Black Kedu, Merawang, and Nunukan chickens for both sexes, of which all the chickens possessed multicolor plumage. Asmara et al [7] found that black was the most predominant plumage color in female Pelung chickens. Meanwhile, other studies have found brown as the common plumage color in Ethiopian chickens [15] and Nigerian chickens [16] and white plumage color as a common feature in Ghanaian chickens [8].…”
Section: Plumage Colormentioning
confidence: 97%
“…The current study indicated that Bajing turun (climbing down squirrels' tailtyped comb) is commonly found in all study areas. A similar finding was stated by Asmara et al (2019) for female Pelung chickens. The local term for chicken traits was also reported by among others, Dana et al (2010) who studies indigenous chickens in Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
“…Pelung chicken is a chicken that was developed in Cianjur [17]. Asmara et al [18] expected Red jungle fowl (Gallus gallus) was the ancestor of Pelung but, there is no data regarding the pedigree of this chicken. From the results obtained in this study, it is suspected that Pelung chickens are the result of cross-breeding.…”
Section: Discussionmentioning
confidence: 99%